Pío del Río Hortega and the discovery of the oligodendrocytes - Fernando ePérez-Cerdá; Fernando ePérez-Cerdá; Fernando ePérez-Cerdá; María Victoria eSánchez-Gómez; María Victoria eSánchez-Gómez; María Victoria eSánchez-Gómez; Carlos eMatute; Carlos eMatute; Carlos eMatute (Frontiers Media S.A., 2015)
Pío del Río Hortega (1882-1945) discovered microglia and oligodendrocytes and was after Ramón y Cajal, the most prominent figure of the Spanish school of neurology. He began his scientific career with Nicolás Achúcarro with whom he learned the use of metallic impregnation techniques suitable to study non neuronal cells. Later on, he joined Cajal´s laboratory, and afterwards he created his own group where he continued developing other innovative modifications of the silver staining methods that revolutionised the study of glial cells a century ago. He was at that time also interested in neuropathology and became a leading authority in Central Nervous System (CNS) tumours. In parallel to this clinical activity, del Río Hortega rendered the first systematic description of the great polymorphism present in a subtype of macroglial cells that he named himself as oligodendroglia and later oligodendrocytes. He established their ectodermic origin and suggested that they build the myelin sheath of CNS axons, just as Schwann cells do in the periphery. Notably, he also suggested the trophic role of oligodendrocytes for neuronal functionality, an idea that it has been substantiated in the last few years. Del Río Hortega became internationally recognized and established an important neurohistological school with outstanding pupils from Spain and abroad, which nearly disappeared after his exile due to the Spanish civil war. Yet, the difficulty of metal impregnation methods and their variability in results, delayed for some decades the confirmation of his great insights into oligodendrocyte biology until the development of electron microscopy and immunohistochemistry. This review aims at summarizing the pioneer and essential contributions of del Río Hortega to the current knowledge of oligodendrocyte structure and function, and to provide a hint of the scientific personality of this extraordinary and insufficiently recognized man.